Can tropical farmers reconcile subsistence needs with forest conservation?. Issue 10 (11th March 2009) - Knoke, Thomas; Calvas, Baltazar; Aguirre, Nikolay; Román-Cuesta, Rosa María; Günter, Sven; Stimm, Bernd; Weber, Michael; Mosandl, Reinhard
Abstract : If tropical farmers cannot be provided with sustainable land‐use systems, which address their subsistence needs and keep them gainfully employed, tropical forests will continue to disappear. We looked at the ability of economic land‐use diversification – with reforestation of tropical "wastelands" as a key activity – to halt deforestation at the farm level. Our ecological–economic concept, based on land‐use data from the buffer area of the Podocarpus National Park in southern Ecuador, shows that stopping deforestation after 10 years is possible without violating subsistence demands. Tropical, farm‐level diversification may not only reduce total deforestation by 45%, but also increase farmers' profits by 65%, because the formerly unproductive wastelands have been returned to productive land use. We therefore conclude that a "win–win" scenario is possible: the subsistence needs of people can be reconciled with conservation objectives. However, inexpensive microcredits (at interest rates below 6%) and experience on alternative land‐use opportunities must be offered to farmers.